Evaluation of the relationship between cardiopulmonary exercise test findings and clinical status in children and adolescents with congenital heart disease - Çetiner, Nilüfer; Çeliker, Alpay (The Turkish Journal of Pediatrics, 2022)
Background. The cardiopulmonary exercise test is accepted as a helpful diagnostic tool in risk stratification, evaluation of prognosis, and guiding treatment modality in adults with congenital heart disease. In this study, we present our experience with the use of cardiopulmonary exercise test in children with congenital heart disease in different physiological and anatomical classifications. Methods. In this retrospective study, 25 children and adolescents who applied to the pediatric cardiology outpatient clinic between 2017 and 2020 with the diagnosis of different types of congenital heart disease were included. Demographic characteristics, electrocardiogram, echocardiogram, cardiopulmonary exercise test, spirometry, pro-BNP values, and in selected 20 patients; cardiac MRI data were examined. The modified Ross classification was used for heart failure grading. Results. The mean age of the patients was 14.8 ±2.39 years. Fifteen (60%) of the patients were male and 10 (40%) were female. In the modified Ross classification, patients in group I-II had significantly higher maximum exercise time, heart rate reserve %, peak VO2, and VO2/kg values compared to those in group III (p=0.026, p=0.007, p=0.043, p= 0.018, respectively). Cardiopulmonary exercise test and spirometry values obtained from the patients were evaluated in the light of clinical and other laboratory findings, and surgical/interventional treatment was decided for 4 patients with the use of these test results. Conclusions. Cardiopulmonary exercise test is a useful noninvasive diagnostic tool in guiding the treatment decision and predicting the prognosis of pediatric patients with congenital heart disease, who have borderline symptoms.
Keywords: Ross classification; cardiopulmonary exercise test; child; congenital heart disease